(untitled) (Academia Journal of Medicine, 2020)
Background: Seizure is defined as “a paroxysmal event due to abnormal excessive or synchronous neuronal activity in the brain.” Based on discharge characteristics and its distribution, this unusual activity can manifest either as focal or generalized tonic clonic to absence seizures which are not easily noticeable by observer. For 2010, as indicated by the Global Burden of Disease (GBD) investigation, epilepsy accounted for 0.7% of burden globally i.e, more than 17 million DALYs. Studies conducted in India have reported variable incidence rates which varies from 0.2 to 0.6 per 1,000 population. The incidence rates reported from India are similar to most of the developed countries and less than most of the developing nations which ranged from 1.0 to 1.9 per 1,000 per year. AIM: The aim of the study is to assess & identify the various clinico-etiological factors causing first onset of seizures in gaeriatric patients. Rationale: Several studies are available on seizure in elderly in western population but very few studies are done in this part of the world. Etiological profile of seizures varies from place to place because of difference in socio-economic and cultural attributes, prevalence of various diseases in a particular area and several other factors. This study aims to observe the clinico-etiological profile of new onset seizures in elderly in Moradabad region of western Uttar Pradesh. Subjects and Methods: This study was carried out at Teerthanker Mahaveer Medical College and Research Centre, Moradabad (UP) as an observational hospital based study. 51 patients of new onset seizures above 60 years of age. Inclusion Criteria: All patients with new onset seizures and were more than 60 years of age. Exclusion Criteria: All patients with age less than 60 years. All known cases of Seizure disorder/Epilepsy were excluded. All those who did not give consent. Results: Out of 51 elderly patients, males accounted for 55%, females accounted for 45% and a gender ratio of 1.2:1 for male to female. Among 51 patients with new-onset seizures, hypertension was seen in 29.4% patients as co-morbidity and 13.7% patients had both hypertension and diabetes as co-morbidities. The study also showed that generalized tonic-clonic seizures (GTCS) were found among 76.5% cases whereas among 23.5% patients were of focal seizures. However, acute and remote symptomatic were almost found in an equal proportion 47.1% and 45.2% respectively and only 7.8% were idiopathic. It was noted that the maximum number of patients had CVA as the cause of new onset seizures in this age group, of which 90.9% patients had an ischaemic stroke. 14 patients had metabolic insult of which, 35.71% patients had uremic encephalopathy as the cause of new onset seizures. 60% of seizures in CNS infections are secondary to tuberculosis probably because of high burden of tuberculosis in the study area. Conclusion: In our study CVA was the frequently observed etiology of seizures among study population and the second most common was metabolic insults. Among stroke, seizures occured more commonly in ischemic stroke than in hemorrhagic stroke. In our study GTCS was the most common type of seizure in 76.5% of study population. And acute symptomatic and remote symptomatic were almost seen in equal numbers 47.1% and 45.2% respectively. CVA accounted for most of the remote symptomatic seizures of which ischemic stroke is most common and metabolic causes accounted for most of the acute symptomatic seizures. The high burden of tuberculosis in the study area may have accounted for this higher percentage (60%) of seizures secondary to tuberculosis in the study patients under CNS infections sub group.